Pengaruh Kualitas Pelayanan dan Persepsi Harga Terhadap Keputusan Pembelian Konsumen Dealer Yamaha Jayamandiri Gemasejati Tasikmalaya - Sopwan Sopyulloh (Kajian Ekonomi dan Akuntansi Terapan, 2024)
The aim of this research is to understand and analyze partially and simultaneously the impact of service quality and price perception on consumer purchasing decisions at the Yamaha Jayamandiri Gemaasejati Tasikmalaya dealer. A quantitative method was applied in this study involving 100 respondents as a consumer survey approach. Data was collected using a questionnaire method. This research applies multiple regression analysis, correlation coefficient, and also uses the coefficient of determination using the SPSS application as data processing. The results of the research show that service quality and price perceptions have an influence on purchasing decisions simultaneously or partially.